Mobile web and intelligent information systems : 13th International Conference, MobiWis 2016, Vienna, Austria, August 22-24, 2016, Proceedings /: 13th International Conference, MobiWis 2016, Vienna, Austria, August 22-24, 2016, Proceedings. (2016) - Unknown
No abstract available